Learning Management Based on an Academic Subject Approach in Pesantren - Badrun (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research aims to analyze Pesantren-based learning management at the Nurul Hakim Pesantren Nurul Hakim, West Lombok. This research uses a qualitative method with a descriptive analytical approach. Data was collected through participant observation, interviews, and document analysis. Data were analyzed by data reduction, data presentation, and drawing conclusions. The results of the research show that the Nurul Hakim Pesantren Nurul Hakim, Kediri, West Lombok has an educational program that is prepared independently where this program contains formal, non-formal and informal educational processes that take place throughout the day in one condition in the dormitory. Thus, Pesantren are institutionally developed to make their impact more effective, Pesantren are not only a place of learning but are a process of life itself, character formation and resource development. With some modifications, a formal teaching system of the classical variety of classroom teaching and an integrated curriculum was implemented. The implications of these findings can be used as a basis for further improvement and development in pesantren-based learning management and increasing the relevance of pesantren education to the demands of the times.